2023
DOI: 10.1177/08258597221149545
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Experiences of Cancer Pain: A Descriptive Qualitative Study

Abstract: Objective The aim of this study was to explore the cancer pain experiences of Iranian patients. Design A qualitative descriptive design was used. Methods This qualitative descriptive study was performed on 17 participants between December 2020 and September 2021. Data were collected using semistructured interviews and analyzed by Graneheim and Lundman's content analysis method. Results Three main categories emerged in relation to patients’ experiences of cancer pain. Categories included (1) characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…In a cross-sectional survey on 156 cancer patients in Hunan Province, China conducted by Xu X et al [ 25 ] found that cancer patients’ acceptance of pain was related to age, gender, marital status, pain duration, number of pain sites and duration of taking analgesics. Hassankhani et al [ 26 ] interviewed 17 Iranian patients with cancer pain about their pain experience, and found that nurses did not only need to ease patients’ physical pain, but also pay attention to their sociocultural and spiritual wellbeing, which was consistent with Orujlu et al’s findings [ 27 ]. Although there have been studies on the degree of acceptance among patients with chronic pain, most of them were quantitative studies with non-cancer pain as the main subjects [ 28 30 ], and little is known about the perceptions, needs, and pain acceptance of advanced cancer patients with chronic pain.…”
Section: Introductionsupporting
confidence: 59%
“…In a cross-sectional survey on 156 cancer patients in Hunan Province, China conducted by Xu X et al [ 25 ] found that cancer patients’ acceptance of pain was related to age, gender, marital status, pain duration, number of pain sites and duration of taking analgesics. Hassankhani et al [ 26 ] interviewed 17 Iranian patients with cancer pain about their pain experience, and found that nurses did not only need to ease patients’ physical pain, but also pay attention to their sociocultural and spiritual wellbeing, which was consistent with Orujlu et al’s findings [ 27 ]. Although there have been studies on the degree of acceptance among patients with chronic pain, most of them were quantitative studies with non-cancer pain as the main subjects [ 28 30 ], and little is known about the perceptions, needs, and pain acceptance of advanced cancer patients with chronic pain.…”
Section: Introductionsupporting
confidence: 59%